Impact of the Tobacco Heating System and Cigarette Smoking on the Oral Cavity: A Pilot Study - Ella Sever; Elvis Božac; Ema Saltović; Sunčana Simonić-Kocijan; Martina Brumini; Irena Glažar (MDPI AG, 2023)
Cigarette smoking and the harmful chemicals released during smoking have negative effects on oral health. As a measure of harm reduction, a new alternative tobacco heating system (THS) has been developed. The aim of the study was to analyze and compare the effects of conventional cigarettes and THS on the oral mucosa, the salivary flow rate (SFR), halitosis, and the load of Candida spp. The study included 20 tobacco heating smokers, 20 conventional cigarette smokers, and 20 nonsmokers. The subjects completed questionnaires on medical information, smoking habits, oral lesions, and symptoms. A clinical examination and SFR test were performed on each subject, followed by an organoleptic assessment of halitosis. Mucosal swabs were collected and cult ured to identify Candida spp. Significant differences were found between the smoking groups in relation to halitosis (p < 0.001; ε2 = 0.624), intraoral findings (p < 0.001; ε2 = 0.507), SFR (p < 0.001; ε2 = 0.0331) and dry mouth for subjective complaints (p = 0.021; ε2 = 0.363). The SFR was significantly lower; however, halitosis, the prevalence of intraoral findings, and dry mouth were significantly higher among smokers, but there were no significant differences between THS and conventional smokers. The present study suggests that THS smoking has similar effects on oral tissues, especially the SFR and halitosis, as conventional cigarette smoking.